2007
DOI: 10.1210/en.2007-0797
|View full text |Cite
|
Sign up to set email alerts
|

Pro-Opiomelanocortin Modulates the Thermogenic and Physical Activity Responses to High-Fat Feeding and Markedly Influences Dietary Fat Preference

Abstract: Complete proopiomelanocortin (POMC) deficiency causes a human syndrome of hypoadrenalism, altered skin and hair pigmentation, and severe hyperphagic obesity. Heterozygote carriers of nonsense mutations are strongly predisposed to obesity. Pomc(+/-) mice have normal body weight on a chow diet but increase food intake and become more obese than wild-type littermates when placed on a high-fat diet. To further explore the mechanisms whereby dietary fat interacts with Pomc genotype to produce obesity, we examined P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…For example, Tung et al 2007 compared POMC −/− mice with wildtype mice of a 129/SvEv background provided HFD and observed increases in both SPA and EE [14]. The difference in SPA results between that investigation and the present study may be due to strain differences.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…For example, Tung et al 2007 compared POMC −/− mice with wildtype mice of a 129/SvEv background provided HFD and observed increases in both SPA and EE [14]. The difference in SPA results between that investigation and the present study may be due to strain differences.…”
Section: Discussionmentioning
confidence: 51%
“…For example, several studies have shown a decrease in physical activity during exposure to high-fat diet (HFD), with others showing the opposite effect, suggesting this relationship may be complex [914]. Similarly, total EE may also be affected by the type of diet available, with studies showing both increases and decreases in energy expenditure in animals with access to HFD compared to chow and low-fat diets [9, 14, 15]. In addition, there have been no studies to date which have assessed the effect of chow-feeding vs. HFD specifically on NEAT, which is important for understanding the diet-based relative contribution of SPA to energy expenditure.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the opposite was the case, and EE and LA were even lower in rats fed the LC-HF diets. The observed reductions in LA during the dark phase could also be due to an altered eating behavior of the LC-HF groups, since it is known that the central mechanism associated with eating behavior can affect LA (40,47,48). Interestingly, investigations in humans have shown that study subjects consuming LC-HF diets often feel tired and exhausted (14), which potentially could lead to reduced LA.…”
Section: E73 Ketosis Induction With Low-carbohydrate/high-fat Diets Imentioning
confidence: 98%
“…Flavonoids as one of the most diverse and widespread groups of natural compounds are probably the most important natural phenolics (Agrawal, 1989). These compounds possess a broad spectrum of chemical and biological activities including radical scavenging properties (Tung et al, 2007), such properties are especially distinct for flavonols (Miliauskas et al, 2004).…”
Section: Total Phenolic Flavonoid Proanthocyanidin and Flavonol Conmentioning
confidence: 99%